Effectiveness Of Amino Acid Formula For Management Of Cow's Milk Allergy In Infants And Children - Sundjaya, Tonny; Purnomosari, Lupi; Fadil Himawan, Muhammad; Wulandari, Alifah (Ridwan Institute, 2024)
Cow's milk allergy is one of the significant health problems in infants and children that impacts their quality of life. As a solution, amino acid-based infant formula has become an innovative alternative to address this challenge. However, the effectiveness of their use requires further substantiation through previous studies. This study aims to evaluate the effectiveness of amino acid-based formula in the management of cow's milk allergy in infants and children. The results showed that amino acid-based formula is an effective solution in managing cow's milk allergy. It is completely allergen-free, easy to digest, and supports optimal growth and development of infants and children. The use of this formula significantly reduces allergy symptoms by avoiding exposure to cow's milk protein, while improving the quality of life of infants and children with cow's milk allergy. Thus, the results of this study confirm the importance of amino acid-based formulas as a safe and efficient treatment option for infants and children with cow's milk allergy.